2020
DOI: 10.1111/fire.12246
|View full text |Cite
|
Sign up to set email alerts
|

Executive risk incentives, product market competition, and R&D

Abstract: Prior studies have examined the relation between product market competition (PMC) and research and development (R&D) investments, while the impact of executive risk incentives on this relation remains unexplored. In this study, we find that Vega (the sensitivity of executives’ wealth to stock return volatility) weakens the negative relation between PMC and R&D. We also find that Vega strengthens the negative relation between PMC and firm performance when R&D investments grow higher. In sum, our results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…A one standard deviation increase in financial expert ratio reduces underinvestment in high‐growth firms and in those operating in a more competitive environment by an additional 6% from the average underinvestment level (0.027 × 0.141/0.065), hence approximately doubling the effect of TMT's financial expertise. It is perhaps unsurprising that we do not find a more significant impact of financial expert managers on overinvestment in high‐growth, financially constrained and more competitive firms, as it is underinvestment, rather than overinvestment, that poses a serious problem in these firms (Abdoh & Liu, 2021; Gay & Nam, 1998; Myers, 1977). Overall, this evidence supports hypotheses 2A–2C that having more financial experts on TMT is especially valuable for firms who suffer from greater investment inefficiencies.…”
Section: Resultsmentioning
confidence: 84%
“…A one standard deviation increase in financial expert ratio reduces underinvestment in high‐growth firms and in those operating in a more competitive environment by an additional 6% from the average underinvestment level (0.027 × 0.141/0.065), hence approximately doubling the effect of TMT's financial expertise. It is perhaps unsurprising that we do not find a more significant impact of financial expert managers on overinvestment in high‐growth, financially constrained and more competitive firms, as it is underinvestment, rather than overinvestment, that poses a serious problem in these firms (Abdoh & Liu, 2021; Gay & Nam, 1998; Myers, 1977). Overall, this evidence supports hypotheses 2A–2C that having more financial experts on TMT is especially valuable for firms who suffer from greater investment inefficiencies.…”
Section: Resultsmentioning
confidence: 84%
“…When executives believe that their stock options provide high expected returns, this expected wealth effect may offset (at least partially) the negative impact of their current wealth on high-risk strategic choices. Abdoh and Liu (2021) suggested that high Vega (the sensitivity of executives' wealth to stock return volatility) increases the motivation of executives to invest in R&D. Their results indicated that Vega weakens the negative correlation between product market competition and R&D investment.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This study controls for variables related to firm characteristics. Previous studies have shown that the following variables significantly affect corporate R&D investment: firm size, expressed as a natural logarithm of the total number of firm employees (Howell, 2016); firm age, expressed as a natural logarithm of the number of years since the firm's establishment (Midavaine et al, 2016); firm performance (Greve, 2003;Su and Su, 2017), expressed in terms of return on equity; independent director size, expressed as the proportion of the board comprising independent directors; CEO duality (Lim, 2015), a dummy variable coded as 1 if the CEO also holds the position of board chairperson and 0 otherwise; state ownership (Zhou et al, 2017), a dummy variable coded as 1 if a firm is a state-owned enterprise and 0 otherwise; and cash compensation (Abdoh and Liu, 2021), expressed as a natural logarithm of the total cash compensation of top managers. Firm leverage and product market competition are also controlled.…”
Section: Control Variablesmentioning
confidence: 99%
“…With size of businesses growing gradually, modern corporations have an increasingly urgent demand for capital and management skills. Yet, while a chief executive officer (CEO) is hired to improve management efficiency, various agency problems may arise as a result of the conflict of interests between the manager's self‐interests and those of the shareholders who are concerned with enhancing firm value (Abdoh & Liu, 2021; Chen et al, 2022; Jensen & Meckling, 1976). In order to mitigate the agency conflicts between managers and shareholders, prior researchers have provided a number of control mechanisms, such as supervision by external shareholders (e.g., Ali & Zhang, 2015; Demsetz & Lehn, 1985), supervision by the board of directors (e.g., Ding et al, 2010; Khan et al, 2022), and managerial compensation plans (e.g., Bettis et al, 2018; Huang et al, 2022; Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%